2021
DOI: 10.3390/s21206785
|View full text |Cite
|
Sign up to set email alerts
|

Automated ELISA On-Chip for the Detection of Anti-SARS-CoV-2 Antibodies

Abstract: The COVID-19 pandemic has been the most critical public health issue in modern history due to its highly infectious and deathly potential, and the limited access to massive, low-cost, and reliable testing has significantly worsened the crisis. The recovery and the vaccination of millions of people against COVID-19 have made serological tests highly relevant to identify the presence and levels of SARS-CoV-2 antibodies. Due to its advantages, microfluidic-based technologies represent an attractive alternative to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Advanced optical sensor technologies (Table 3) such as photonic [27] and surface plasmon resonance sensors [28,29] are able to provide results within 10 min, whereas more traditional approaches require more time (LFA, ELISA, 15-60 min) [30,31].On the other hand, electrochemical sensors require a mean response time of approximately 30 min [32][33][34][35][36]. Taking into account the above-mentioned, our biosensor is able to detect SARS-CoV-2 antibodies in an ultra-rapid manner (3 min) and at quite low concentrations (5 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced optical sensor technologies (Table 3) such as photonic [27] and surface plasmon resonance sensors [28,29] are able to provide results within 10 min, whereas more traditional approaches require more time (LFA, ELISA, 15-60 min) [30,31].On the other hand, electrochemical sensors require a mean response time of approximately 30 min [32][33][34][35][36]. Taking into account the above-mentioned, our biosensor is able to detect SARS-CoV-2 antibodies in an ultra-rapid manner (3 min) and at quite low concentrations (5 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…The automated enzyme-linked immunosorbent assay (ELISA) on-chip microfluidic platform developed by Gonzalez-Gonzalez et al, the Opto microfluidic sensing platform based on localizes surface plasmon resonance (LSPR) developed by Funari et al, paper-based pulling force spinning top microfluidic devices designed by Gong et al, microfluidic chemiluminescent ELISA technique by Tan et al, and the reciprocating flowing immunobinding strategy by Liu et al detect anti-SARS-CoV-2 antibodies by spectrometer-based detection techniques ( Table 1 ) [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Microfluidics In Sars-cov-2mentioning
confidence: 99%
“…Gonzalez-Gonzalez et al, Liu et al, and Gong et al reported the use of commercial smartphone cameras to take photographs of the resulting colorimetric reactions and analyze the images with ImageJ software to detect and quantify the antibody concentrations with a high limit of detections. In contrast, the Opto microfluidic sensing platform developed by Funari et al and the microfluidic chemiluminescent ELISA-based platform designed by Tan et al require comparatively complex and extensive analyzing equipment NanoDrop One UV-Vis spectrometer (Thermo Fisher’s, USA) and CMOS camera along with ImageJ software (NIH, Bethesda, MD, USA) [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Microfluidics In Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve quantitative measurement while maintaining a simple and user-friendly interface, attempts have been made to conduct immunoassays in miniaturized devices (28) using principles such as ELISA (29)(30)(31), electrochemistry (32,33), surface plasmon resonance (34), and fluorescence (35)(36)(37)(38). However, signal quantification requires additional detection modules, e.g., optical fibers, light source, amperemeters, or photodetectors, for measuring optical absorbance or fluorescence intensity.…”
Section: Introductionmentioning
confidence: 99%